Pitaya (Hylocereus undatus) initial growth in function to NPK fertilization - Gonçalves, Ana Flávia Matias; Pinto, Sheila Isabel do Carmo; Corrêa, Ricardo Monteiro (Revista Agrogeoambiental, 2020)
Pitaya is considered a very promising cactus fruit, however, there is a lack of studies that support the definition of more suitable production systems. Thus, the objective of this work was to evaluate the effect of NPK mineral fertilization on pitaya initial growth, aiming the definition of nutritional and fertilization management appropriate to the agricultural exploitation of the crop. The assay was conducted in the greenhouse of the Biotechnology Laboratory. The propagating part of pitaya is its stem known as cladode. The cladodes were planted in pots of 8.0 dm3, filled with substrate based on soil from termites. The donor matrices of vegetative material were young specimens of white-fleshed pitaya (Hylocereus undatus). 72 cuttings of 30.0 cm in length were used. The experimental design was in randomized blocks with 9 treatments (NPK doses) and 4 replications, totalizing 36 experimental plots. Each experimental plot was composed of 2 cuttings. Number of cladodes, sum of cladodes length, fresh cladodes mass, dry cladodes mass, root system length, root system fresh mass and root system dry mass were evaluated at 160 days after planting the morphological characters. The results of the variables were submitted to the analysis of variance and the means grouped by the Scott-Knott test at 5% of probability. NPK fertilization affected the initial growth of the aerial part and the root system of pitaya. The greatest development of pitaya was provided by 450.0 mg dm-3 of N, 250.0 mg dm-3 of P and 250.0 mg dm-3 of K.